PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN DI RESTORAN SUSHIMAS - Paskah Amelia Situmeang; Bonifasius MH Nainggolan; Al. Agus Kristiadi (LPPM and Travel Operation Department Universitas Asa Indonesia, 2020)
This study's purpose of determining the effect of product quality, service quality, and trust in customer satisfaction at Sushimas Restaurant. The data collection was conducted through a questionnaire survey of 100 selected Sushimas Restaurant customers using the purposive sampling method. Data processing uses multiple linear regression analysis methods. The analysis results showed that product quality, service quality, and trust have a significant positive effect on customer satisfaction. Of the three variables studied, trust has better explained the variability of customer satisfaction, followed by service quality and product quality. The three variables simultaneously explain that customer satisfaction variability is 31.02%, while the remaining 68.98% is affected by other variables not included in this research variable